Tracing the source of marine debris on the beaches of northern New South Wales, Australia: The Bottles on Beaches program. (January 2018) - Smith, Stephen D.A.; Banister, Kelsey; Fraser, Nicola; Edgar, Robert J.
Abstract: Identifying the source of marine plastic pollution accumulating on ocean beaches is often difficult as unidentifiable fragments of plastic usually predominate. In this study, we surveyed plastic bottles as a relatively identifiable subset of plastics on 30 km of beach along a 200-km section of the north coast of New South Wales, Australia. Source and product type (contents) were determined using barcodes, inscriptions/embossing, or bottle shape and characteristics. Country of origin and product type could be determined for two-thirds of the 694 bottles found. Just over half (51%) of these were of domestic origin with the remainder dominated by bottles from China (24%) and south-east Asian countries (21%). As most of the foreign bottles lacked marine growth, and are unavailable for purchase in the region, passing ships are hypothesised as the primary source. Highlights: Plastic bottles were collected from beaches on the NSW north coast. Sources and product types (contents) were subsequently determined. 49% were from foreign sources but few possessed marine growth. Merchant shipping is therefore the most likely source of foreign bottles.